Peaceful social testing in times of increasing individualization and isolation. Issue 1 (2nd January 2019) - Murphey, Tim
ABSTRACT: A conception of social testing is described in which students are directed to give themselves grades at two moments: first, after filling in answers that they recall alone; second, after asking others in the class for mediating help during social interaction. The first grade is an estimate of individual efforts, without social connections. The second grade represents a situated person in a community with developing connections, something neurologists, sociologists, and anthropologists see as an ecological step towards species well-being (Murphey 2017a, 2017b). Social testing is one step toward changing an epidemic trend in our societies and schools toward increasing individualization and isolation (III).